Faktor Penentu Kepuasan Pelanggan pada Layanan Marketplace Shopee di Jakarta Barat - Andira Hadi Wibisono; Aditiya Pratama Nugroho (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2026)
The rapid advancement of information technology has significantly changed how people engage in transactions, especially through e-commerce platforms. Among these, Shopee stands out as one of the most widely used marketplaces in Indonesia. This research explores the key factors that affect customer satisfaction with Shopee’s services in the West Jakarta area. A quantitative approach with an associative design was applied, involving 60 participants selected through purposive sampling based on specific criteria. The independent variables examined include service quality, ease of use of the application, and promotions, while customer satisfaction serves as the dependent variable. Multiple linear regression analysis using SPSS 25.0 revealed a constant value of 3.331, indicating a baseline level of customer satisfaction. The coefficient for service quality was 0.149 (p > 0.05), indicating an insignificant effect. In contrast, ease of use had a coefficient of 0.231 with a significance value of 0.022, and promotion had the highest coefficient at 0.395 with a p-value of 0.001. This outcome suggests that both variables significantly influence customer satisfaction. The F-test also showed an F-value of 21.184 with a significance level of 0.000 (< 0.05), confirming that the regression model is suitable for predicting customer satisfaction. These findings suggest that strategies aimed at enhancing application usability and intensifying promotional efforts play a more crucial role in increasing Shopee customer satisfaction than improvements in service quality. The study recommends that Shopee's management focus on developing user-friendly access and promotional strategies to maintain customer loyalty, especially in highly competitive urban markets like West Jakarta.